Design and Analysis for the Double-roller Gear Longitudinal Torsional Compound Ultrasonic Rolling System - Jinhao Gao; Wen Shao; Yuhui He; Jinyuan Tang (Jixie chuandong)
This study attempts to solve the problems such as low efficiency and relatively small range due to the constraints of device and monotony of vibration in ultrasonic assisted rolling of gears. A novel double-roller longitudinal torsional compound gear ultrasonic rolling system including a longitudinal torsional compound horn and its matching tool gear is proposed. Through the theoretically calculation method， the frequency equation of the horn is derived and the relevant design parameters are calculated. The longitudinal torsional compound vibration displacement and trajectory at the tooth surface are calculated by FEM with spiral grooves in the conical section and the assembled gear. The influences of different parameters of spiral groove such as number， depth， width and helical angle of the groove on torsional longitudinal compound vibration is analyzed by univariate method， FEM and an introduced parameter torsional longitudinal vibration ratio. The optimal parameter combination is obtained and the tool the gear is designed by using lightweight design method. The results show that the design of compound horn meets the requirements， and the effective longitudinal torsional compound vibration of the assembled gear is obtained. The longitudinal torsional compound vibration can be generated with spiral grooves in the conical section. The torsional vibration is mainly related to the number， depth， width and helical angle of the grooves. The double-roller gear longitudinal torsional compound ultrasonic rolling system is obtained by assembling with tool gear， it provides a technical support for the performance of the new gear longitudinal-torsional ultrasonic rolling device.